2016
DOI: 10.11609/jott.1888.8.9.9144-9154
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous ornamental freshwater ichthyofauna of the Sundarban Biosphere Reserve, India: status and prospects

Abstract: Ornamental fishes are the most popular pet throughout the world and high demand for these fishes has made them an important component of the world fish trade. India contributes a very meager percentage to the world ornamental fish trade; but considering the high ichthyofaunal diversity it has the potential to compete with the world’s leading ornamental fish producers in the near future. Sundarban Biosphere Reserve has abundant waterbodies with rich fish diversity. Although some research has been carried out on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Badis badis (Hamilton,1822) (Actinopterygii: Perciformes) also known as Badis, is a small tropical benthopelagic fish from the Badidae family [ 1 , 2 ]. This fish species is used as for decorative purposes and exploited for the aquarium business because of its appealing and colorful pattern [ 3 , 4 ]. This species inhabits freshwater and is mostly found in rivers, ponds, channels, and swamps [ 5 , 6 ], available in waters with aquatic vegetation [ 7 ] and also widespread in South Asia's streams, especially in Bangladesh, India, and Nepal [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Badis badis (Hamilton,1822) (Actinopterygii: Perciformes) also known as Badis, is a small tropical benthopelagic fish from the Badidae family [ 1 , 2 ]. This fish species is used as for decorative purposes and exploited for the aquarium business because of its appealing and colorful pattern [ 3 , 4 ]. This species inhabits freshwater and is mostly found in rivers, ponds, channels, and swamps [ 5 , 6 ], available in waters with aquatic vegetation [ 7 ] and also widespread in South Asia's streams, especially in Bangladesh, India, and Nepal [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on this species tend to focus on its taxonomy, behavior, and ecology rather than its economic significance in fisheries. Some available studies ( Table 1 ) have been conducted on this species, including intra-population diversity [ 17 ], genetic diversity [ 18 ], population and hierarchical genetic structure [ 19 ], genetic diversity and population differentiation analysis [ 20 ], analyses of genetic diversity [ 21 ], new record of Blue Perch [ 22 ], effects of carotenoid supplementation [ 23 ], feeding and reproductive biology [ 1 ], mosquito control [ 24 ], indigenous ornamental freshwater [ 25 ], biological parameters [ 26 ], length-weight relationships [ 27 , 28 ], and morphological characterization [ 29 ]. There are no previous studies on population dynamics and stock status of B. badis that have been carried out in our studied ecosystem of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…The ornamental sh trade is a pro table alternative wealth generating business in the aquaculture sector (Gupta et al 2016). Despite having a large production through intensi ed culture practices, culturists struggle to meet market demand due to the presence of various infectious diseases, leading to huge sh mortality thereby substantial nancial losses (Chanda et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Bhuiyan (1964) and Memon et al (2010) also reported that C. garua is mostly consumed by various group of people including the marginalized people due to high level of protein (18.40%) and fat (5.2%) content, followed by most abundant in some of the river system (Galib et al 2009). Besides these, the species also has ornamental values that promotes livelihood of the coastal communities (Gupta et al 2016).…”
mentioning
confidence: 99%